The Phosphate Inhibition Paradigm: Host and Fungal Genotypes Determine Arbuscular Mycorrhizal Fungal Colonization and Responsiveness to Inoculation in Cassava With Increasing Phosphorus Supply - Peña Venegas, Ricardo Alexander; Lee, Soon-Jae; Thuita, Moses; Mlay, Deusdedit Peter; Masso, Cargele; Vanlauwe, Bernard; Rodriguez, Alia; Sanders, Ian R. (Frontiers in Plant Science, 2021)
A vast majority of terrestrial plants are dependent on arbuscular mycorrhizal fungi (AMF) for their nutrient acquisition. AMF act as extension of root system helping phosphate uptake. In agriculture, harnessing the symbiosis can potentially increase plant growth. Application of the AMF Rhizophagus irregularis has been demonstrated to increase yields of various crops. However, there is a paradigm that AMF colonization of roots, as well as plant benefit afforded by inoculation with AMF, decreases with increasing P supply in soil. The paradigm suggests that when fertilized with sufficient P, inoculation of crops would not be beneficial. However, the majority of experiments demonstrating the paradigm were conducted in sterile conditions without a background AMF or soil microbial community. Interestingly, intraspecific variation in R. irregularis can greatly alter the yield of cassava even at a full application of the recommended P dose. Cassava is a globally important crop, feeding 800 million people worldwide and a crop that is highly dependent on AMF for P uptake. In this study, field trials were conducted at three locations in Kenya and Tanzania using different AMF and cassava varieties under different P fertilization levels to test if the paradigm occurs in tropical field conditions. We found that AMF colonization and inoculation responsiveness of cassava does not always decrease with an increased P supply as expected by the paradigm. Our results demonstrate that maximizing inoculation responsiveness of cassava is not necessarily only in conditions of low P availability, but that this is dependent on cassava variety and fungal variety. Thus, the modelling of plant symbiosis with AMF under different P level in nature should be re-considered.